Moving Forward: Towards a rights-based paradigm for young people transitioning out of care. (January 2017) - Quinn, Neil; Davidson, Jennifer; Milligan, Ian; Elsley, Susan; Cantwell, Nigel
This article proposes that the new UN Guidelines for the Alternative Care of Children usher in a new international rights-based policy framework for care-leavers. It acknowledges the global nature of the concerns, reviews a growing body of international literature and examines key debates, illustrated by policy orientations and practice examples drawn from the authors' experience of developing Moving Forward (Cantwell, Davidson, Elsley, Milligan, and Quinn, 2012), the Guidelines ' international implementation handbook. A number of themes emerge, particularly the value of intangible emotional supports for young care-leavers. The traditional lack of a rights-oriented discourse in this area suggests more strategic collaborative efforts by a range of actors are needed.